Permanent CSF shunting after intraventricular hemorrhage in the CLEAR III trial. (25th July 2017) - Murthy, Santosh B.; Awad, Issam; Harnof, Sagi; Aldrich, Francois; Harrigan, Mark; Jallo, Jack; Caron, Jean-Louis; Huang, Judy; Camarata, Paul; Lara, Lucia Rivera; Dlugash, Rachel; McBee, Nichol; et al.
Abstract : Objective: To study factors associated with permanent CSF diversion and the relationship between shunting and functional outcomes in spontaneous intraventricular hemorrhage (IVH). Methods: Clot Lysis Evaluation of Accelerated Resolution of Intraventricular Hemorrhage (CLEAR III), a randomized, multicenter, double-blind, placebo-controlled trial, was conducted to determine if pragmatically employed external ventricular drainage (EVD) plus intraventricular alteplase improved outcome, in comparison to EVD plus saline. Outcome measures were predictors of shunting and blinded assessment of mortality and modified Rankin Scale at 180 days. Results: Among the 500 patients with IVH, CSF shunting was performed in 90 (18%) patients at a median of 18 (interquartile range [IQR] 13–30) days. Patient demographics and IVH characteristics were similar among patients with and without shunts. In the multivariate analysis, black race (odds ratio [OR] 1.98; 95% confidence interval [CI] 1.18–3.34), duration of EVD (OR 1.10; CI 1.05–1.15), placement of more than one EVD (OR 1.93; CI 1.13–3.31), daily drainage CSF per 10 mL (OR 1.07; CI 1.04–1.10), and intracranial pressure >30 mm Hg (OR 1.70; CI 1.09–2.88) were associated with higher odds of permanent CSF shunting. Patients who had CSF shunts had similar odds of 180-day mortality, while survivors with shunts had increased odds of poor functional outcome, compared to survivors without shunts. Conclusions: Among patients with spontaneous IVH requiring emergency CSF diversion, those with early elevated intracranial pressure, high CSF output, and placement of more than one EVD are at increased odds of permanent ventricular shunting. Administration of intraventricular alteplase, early radiographic findings, and CSF measures were not useful predictors of permanent CSF diversion.